Chronic inflammation and microflora in ENT organs in patients with multiple sclerosis - A. V. Teplov; I. I. Klimova; A. V. Subbotin; Ye. G. Arefiyeva (Бюллетень сибирской медицины)
The paper presents the results of the analysis of nasal cavity and stomatopharynx condition in the group of patients with multiple sclerosis. Microflora, immunological status and inflammatory changes of mucous membranes are studied. In the group of patients with multiple sclerosis the frequency of dysbiotical changes and chronic ENT diseases is higher than in the group of comparison. The correlation between frequency of dysbiosis and immunological status disturbances is shown.